Life and Adventures of Jack Engle : An Auto-Biography; A Story of New York at the Present Time in which the Reader Will Find Some Familiar Characters - Whitman, Walt, 1819-1892 (Book collections on Project MUSE., 2017)
In 1852, young Walt Whitman was working on two books. One would become one of the most famous volumes of poetry in American history, Leaves of Grass. The other, a novel, would be published under a pseudonym and serialized in a newspaper. This is that novel, a short, rollicking story of orphanhood, avarice, and adventure in New York City.